Combined coagulation and inflammation markers as predictors of venous thrombo-embolism and death in COVID-19 - Zhu, Jaja; Bouzid, Raïda; Travert, Benoît; Géri, Guillaume; Cohen, Yves; Picod, Adrien; Heming, Nicholas; Rottman, Martin; Joly-Laffargue, Bérangère; Veyradier, Agnès; Capron, Claude; Coppo, Paul (Frontiers in Medicine, 2024)
Background. The COVID-19 pandemic related to SARS-CoV-2 virus was responsible for global pandemic. The severe form of the disease was linked to excessive activation of immune pathways together with a systemic cytokine storm response and thrombotic venous or arterial complications. Objectives. We investigated the role of prognostic factors from the coagulation or inflammatory pathways to better understand the outcome of the disease. Factors predicting severe outcomes including venous thrombosis (VT) and death were identified, but the prognostic role of their combination was not addressed extensively. Methods. For this, we prospectively studied 167 SARS-CoV-2-positive patients from admission in intensive care units (ICU) or emergency departments from four academic hospitals over a 14-month period. Besides standard biology, we assessed serum concentrations of inflammatory markers, coagulation factors and peripheral blood cells immunophenotyping. Results. Thirty-nine patients (23.3%) developed VT and 30 patients (18%) died. By univariate analysis, CRP level > 150 mg/L, IL-6 ≥ 20 pg/mL, D-dimers > 1500 µg/L, ADAMTS13 activity ≤50%, VWF:Ag ≥ 400, VWF:CB ≥ 350 and VWF:Ag/ADAMTS13 activity ratio ≥ 10 were associated with VT, ICU admission or death. Using these thresholds, a scoring system was built by logistic regression based on the odds ratios derived from CRP, VWF, IL-6 and ADAMS13 activity. This score was discriminant to predict ICU requirement, death and VT. Conclusions. A combination of coagulation and inflammatory markers can refine the prognostication of severe outcome in COVID-19, and could be useful for the initial evaluation of other types of viral infection.